The Structure of Value Orientations of Modern Russian Families: The Regional Dimension of the Problem - Kuzina, Irina Gennadievna; Vinokurova, Anna Viktorovna (International Review of Management and Marketing, 2016)
The article discusses the value systems of families in the context of transformation processes taking place in contemporary Russian society. The main results of the regional empirical study of value systems of families (on the example of Primorsky Territory) were analyzed. The relationship between the family values and values of professional employment was also revealed. A formal questionnaire survey was used as the primary method of sociological data collecting. The study has theoretical and applied aspects, was implemented in line with intelligence and narrative strategy. The results of the conducted research showed that the family in contemporary society is one of the most important human life values. The vast majority of the respondents noted the positive role of the family in human adaptation to social changes which are characteristic of contemporary Russian society. It was also found out that the gender aspect is a major determinant of the degree of person's satisfaction with combination of the family responsibilities with the professional ones. In the course of professional activity high salary is the most important aspect of labour for a considerable part of the respondents. In general, in the structure of value systems of families, living in the Primorsky Territory, the family values are dominant and the values of work and professional employment are inferior. Keywords: family, values, value systems, social transformation, professional employment. JEL Classifications: I390, J130, J240